Land : how the hunger for ownership shaped the modern world - Winchester, Simon (Harper, an imprint of HarperCollinsPublishers, 2021)
Explores the concept of land ownership and how it has shaped history, examining how people fight over, steward, and occasionally share land, and what humanity's proprietary relationship with land means for the future.